Safety Outcomes With Home Assessment Trial: A Mixed-Methods Evaluation of Medication Safety in the Home Care Setting. Issue 2 (May 2018) - Flanagan, Priti S.; Briseño-Garzón, Adriana; Zed, Peter J.; Strain, Robert M.
Adverse drug events (ADEs), a subset of AEs (adverse events), occur among home care recipients, yet the topic of medication safety in this setting is understudied and under reported. The Safety Outcomes With Home Assessment Trial (SO WHAT) was a mixed-methods, pilot study that sought to evaluate the feasibility of prospective evaluation and inform future research in the home care setting to better understand medication use and safety. Over 21 months, 19 patients were recruited. Feasibility of the study was improved by focused recruitment efforts and connection with primary care. All participants had medication issues identified by the pharmacist's medication review and almost half had a suspected ADE. Patient experience themes identified related to knowledge about medications, communication, and home care human resources.